2019
DOI: 10.1142/s0192415x19500253
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chinese Medicine in Health Maintenance and Disease Prevention: Application of Constitution Theory

Abstract: Traditional Chinese medicine (TCM) has guided health maintenance and disease treatment for thousands of years and has been widely used in many countries around the world. TCM regards each individual as unique so all corresponding therapeutic and preventive approaches in TCM are personalized. Personalized medicine, also referred to as precision medicine, is an emerging medical paradigm that points toward a new direction for future medical development. TCM constitution studies the holistic body condition, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 46 publications
2
77
0
1
Order By: Relevance
“…Herbal remedies have been used for centuries for the healing of numerous conditions in different cultures worldwide [79]. They are the imprint of the local cultures, unique regional vegetation, and ancient medicine knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal remedies have been used for centuries for the healing of numerous conditions in different cultures worldwide [79]. They are the imprint of the local cultures, unique regional vegetation, and ancient medicine knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…TCM constitution is distinctive manifestations of inherited and acquired features of human body [32] and affected by demographical characteristics of people. Previous study found that phlegm-dampness constitution was common in well-educated groups, while types of yin-deficiency and yang-deficiency were common in less-educated groups [22].…”
Section: Discussionmentioning
confidence: 99%
“… 2000 ). MsPGN is one of the most common pathological types of chronic glomerulonephritis in Chinese populations (Li 1989 ; Cheng et al. 2009 ).…”
Section: Discussionmentioning
confidence: 99%